INTEGRATING TECHNOLOGY, PLAY, AND COMMUNICATION IN CHILDREN’S LANGUAGE EDUCATION - ABDUKARIMOVA, Khojirakhon (The Lingua Spectrum, 2025)
The rapid development of technology and the increasing demand for global communication have transformed language teaching, particularly for young learners. Modern classrooms now prioritize learner-centered, interactive, and technology-enhanced methods that promote communication, creativity, and autonomy. This paper examines several innovative strategies in children’s language education, including Communicative Language Teaching, Task-Based Learning, Project-Based Learning, Total Physical Response, gamification, and multisensory approaches. Special attention is given to kinesthetic and tactile learning methods widely used in early childhood programs and private language centers highlighting their effectiveness in vocabulary development, comprehension, and learner motivation.